Gambaran Motivasi Berprestasi, Efikasi Diri, dan Kemampuan Adaptasi pada Mahasiswa Semester 1 D3 Keperawatan Politeknik Negeri Indramayu - Nafisah Itsna Hasni; Evi Supriatun; Ike Puspitaningrum; Sally Yustinawati Suryatna; Sukma Diani Putri (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
First year university students would experience a transition period from high school to college. This transition period was a challenge experienced by new students. Several aspects that were influential in overcoming these challenges include achievement motivation, adaptability, and self-efficacy. The aim of this research was to determine the description of achievement motivation, self-efficacy and adaptability in First Semester Students of D3 Keperawatan Politeknik Negeri Indramayu. This research was a descriptive observational study, with the research subjects was 1st semester of D3 Keperawatan Politeknik Negeri Indramayu, totaling 94 students. Data collection techniques in the research used the Achievement Motivation Scale, Self-Efficacy Scale, and Adaptation Ability Scale. The research results showed that the level of achievement motivation, adaptability, and self-efficacy of 1st semester of D3 Keperawatan Politeknik Negeri Indramayu is quite adequate.